2017
DOI: 10.4102/sajim.v19i1.838
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the critical success factors of agile software development projects in South Africa

Abstract: Background: The continued in failure of agile and traditional software development projects have led to the consideration, attention and dispute to critical success factors that are the aspects which are most vital to make a software engineering methodology fruitful. Although there is an increasing variety of critical success factors and methodologies, the conceptual frameworks which have causal relationship are limited.Objective: The objective of this study was to identify and provide insights into the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Based on previous studies done by Guo (2019), Bhoola and Giangreco (2018), Daniel et al (2018), Chiyangwa andEngelbrecht et al (2017), revealed that stakeholder relationship was an important factor in a project, however in this study, apart from stakeholder relationships, another area of concern in regard to stakeholders has been identified important. Stakeholder analysis before engaging in stakeholder relationships, the right stakeholders have to be identified in the first place.…”
Section: Comparison Of These Findings Against Previous Studiesmentioning
confidence: 58%
See 1 more Smart Citation
“…Based on previous studies done by Guo (2019), Bhoola and Giangreco (2018), Daniel et al (2018), Chiyangwa andEngelbrecht et al (2017), revealed that stakeholder relationship was an important factor in a project, however in this study, apart from stakeholder relationships, another area of concern in regard to stakeholders has been identified important. Stakeholder analysis before engaging in stakeholder relationships, the right stakeholders have to be identified in the first place.…”
Section: Comparison Of These Findings Against Previous Studiesmentioning
confidence: 58%
“…Various scholars globally have discussed project time management as a whole. Chiyangwa andMnkandla (2017), Omar et al (2016), Gingnell et al (2014), Adzmi andHassan (2018), andYaghoobi (2018) showed the importance of managing the project time. However, less focus was given on time management before the project was awarded, which is the time for the preparation of the RFP response.…”
Section: Comparison Of These Findings Against Previous Studiesmentioning
confidence: 99%
“…Sledi, Ahimnisabwe et al [13], koji su kreirali još jedan važan model i to na osnovu sistematičnog pregleda literature, u kome je identifikovano 37 KFU za projekte razvoja softvera i grupisao ih u organizacione, timske, faktore kupaca i faktore projekata. Chiyangwa & Mnkandla [28] su identifikovali KFU u oblasti agilnih projekata, kreirali su sledeće kategorije: organizacioni, ljudski, tehnološki i faktori procesa, takođe ispitali su vezu između očekivanih performansi i uspeha agilnih projekata. Sudhakar [12] je predložio jedan od najznačajnijih okvira u oblasti merenja uspeha softverskih projekata, zasnovan na konceptualnom modelu koji je ispitao 80 faktora.…”
Section: Kritični Faktori Uspeha Softverskih Projekataunclassified
“…Nasir and Sahibuddin (2011) have categorised the critical success factors specifically for any software development team and software organisation. Since then, several other studies (Da Silva & Dos Santos, 2017;Fayaz et al, 2017;Ibrahim et al, 2013;Kabir & Rusu, 2016;Kateb et al, 2015;Sudhakar, 2016) Those 26 are not the only critical success factors that affect software development projects, however, they appear at the top of many other studies like in Chiyangwa and Mnkandla (2017).…”
Section: Summary Of Critical Success Factorsmentioning
confidence: 99%